1987
DOI: 10.1017/s0021859600081089
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of changes in soil mineral nitrogen and crop nitrogen during autumn, winter and spring

Abstract: The computer model described simulates changes in soil mineral nitrogen and crop uptake of nitrogen by computing on a daily basis the amounts of N leached, mineralized, nitrified and taken up by the crop. Denitrification is not included at present. The leaching submodel divides the soil into layers, each of which contains mobile and immobile water. It needs points from the soil moisture characteristic, measured directly or derived from soil survey data; it also needs daily rainfall and evaporation. The mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(133 citation statements)
references
References 31 publications
0
133
0
Order By: Relevance
“…As suggested by Addiscott and Whitmore (1987) and Smith et al (1997), to quantify the discrepancy between the simulated and observed results, we adopted three statistical criteria for the validation tests: the coefficient of determination (R 2 , Eq. (14)), the root of mean square error (RMSE, Eq.…”
Section: Statistics For Comparison Between Vpm-predicted and Tower-bamentioning
confidence: 99%
“…As suggested by Addiscott and Whitmore (1987) and Smith et al (1997), to quantify the discrepancy between the simulated and observed results, we adopted three statistical criteria for the validation tests: the coefficient of determination (R 2 , Eq. (14)), the root of mean square error (RMSE, Eq.…”
Section: Statistics For Comparison Between Vpm-predicted and Tower-bamentioning
confidence: 99%
“…Observed values were compared with simulation values to evaluate the accuracy of modeling results using statistical metrics (Rykiel Jr, 1996;Smith et al, 1997;Tonitto et al, 2007). The statistics include modeling efficiency (EF) (Loague and Green, 1991), relative error (E) and mean difference (M) (Addiscott and Whitmore, 1987), and they were applied to determine whether there are significant differences between modeled and measured values. Other statistical tests were also conducted to assess the effects of different treatments on modeled and measured results.…”
Section: Model Validationmentioning
confidence: 99%
“…materials. It varies greatly in space and also in time: a single farmer's field may contain many identifiably different types of soil and the nutrient content, especially of nitrate, may vary from place to place and day to day (Clark et al 2005) owing to the many processes that produce and consume nitrate (Addiscott & Whitmore 1987;Hatch et al 2004;Milne et al 2004). …”
Section: Nutrient Dynamics In Soilmentioning
confidence: 99%
“…This can be advantageous in the case of highly soluble forms of nutrients such as nitrate-N, which is then less able to leach out of the rooting zone (e.g. Addiscott & Whitmore 1987). On the other hand, sufficient quantities of poorly soluble nutrients such as phosphate that diffuse only slowly as a result of a complex structure may not be available or accessible to plant roots (Barraclough 1986).…”
Section: Nutrient Dynamics In Soilmentioning
confidence: 99%